Qualitative study of men's perceptions of why treatment delays occur in the UK for those with testicular cancer. - Chapple, A; Ziebland, S; McPherson, A (2004)
BACKGROUND: Many studies (but not all) have shown that for men with testicular cancer a longer treatment delay is associated with additional treatments, greater morbidity, and shorter survival. AIM: This paper explores patients' perspectives on why treatment delays occur. DESIGN: Qualitative study using narrative interviews SETTING: Interviews in patient's homes throughout the United Kingdom (UK). METHOD: Interviews with a maximum variation sample of 45 men with testicular cancer, recruited through general practitioners (GPs), urologists, support groups, and charities. RESULTS: Those who sought help relatively quickly responded to symptoms, had heard about testicular cancer in the media, had seen leaflets in GPs' surgeries, or knew others with this disease. Men delayed because they did not recognise signs and symptoms; feared appearing weak, a hypochondriac, or lacking in masculinity; recalled past illness or painful examinations; were embarrassed; feared the consequences of treatment; or lacked time to consult their doctors. Beliefs about symptoms and pessimistic associations with cancer also led to delay. Treatment delays also resulted from misdiagnosis or waiting lists. CONCLUSION: Whether or not men should be taught to examine themselves routinely to check for testicular cancer is much debated. This study suggests that it is important that men are aware of the normal shape and feel of their testicles, and may benefit from information about signs and symptoms of testicular cancer and the excellent cure rate. Information, provided in surgeries where men feel welcome, might encourage men to seek help promptly when a problem arises. Our study also suggests that GPs may need to accept a low threshold for ultrasound investigation of testicular symptoms and that the ultrasound service needs to be improved. These measures may further reduce mortality and morbidity.